The motion of the concentration front and adsorption of impurity during pumping of a nanofluid through a porous medium - Demin, Vitaliy Anatol’yevich; Maryshev, Boris Sergeyevich; Menshikov, Aleksandr Igorevich (Computational Continuum Mechanics, 2020)
The direct numerical simulation of the process of filtering a nanofluid through a porous medium of artificial origin is performed. The phenomenon of pore plugging due to the adsorption of nanoparticles on the walls of the channels is investigated. The theoretical study was initiated by the necessity to improve the technological process of saturation of porous materials by powdery media with desired properties. The description of the filtration process is based on Darcy’s law with consideration for the variability of porosity and permeability of the medium, which are related by the Kozeny-Carman formula. The model takes into account the non-linear effect of the backward response to pore plugging, which lies in the fact that the filtration rate essentially decreases causing thereby the enhancement of impurity absorption. Based on the method of finite differences, an algorithm for solving the problem is constructed, and a program code for describing the process of penetration of the suspension into a rectangular sample is developed. The results of numerical simulation are used to plot the fields of velocity, pressure, porosity, permeability, and concentrations of mobile and immobile impurities, which make it possible to trace the dynamics of the filtration process. The obtained numerical results support the observation that the main factor contributing to the flow pattern and pore plugging is the nonlinear interaction between the nanofluid flow and porous material. It is shown that the change in the distribution of immobile impurity in a porous medium is determined by the dynamics of the concentration front, the steepness and speed of which depends on the ratio of the problem parameters (parameters of adsorption-desorption, diffusion coefficient, permeability and pressure difference at the inlet and outlet of the porous material. The results of problem solution obtained within the framework of the advanced MIM model from the beginning of the process to complete pore plugging are used to estimate the time of the technological process, which is found to be in good agreement with experimental data on the saturation of artificial porous materials.